Inheritances of the romanticism in contemporary art: the subjective and representation in concept art artistic production present (Palíndromo, 2014)
The contributions of the Romantic Movement of the late eighteenth century and early nineteenth century, characteri- zed from the evocation of the spirit of fre- edom, the originality of the work, the in- dividual imagination and creativity with no strings attached to the inner world of the artist, there is even the emphasis on emo- tions and the terrible force of nature and especially the break with tradition, contri- buted to a stance on the history of art, now appreciated once disowned by later artistic movements. Knowing the whole process of exchange and permanence, this article seeks to identify the theoretical approach of romantic subjectivity reflections on the emergence of contemporary conceptual art representation.
Keywords: romanticism; contemporary art; representation